Self-Repair Techniques Point to Robots That Design Themselves. - Edwards, Chris (Communications of the ACM, 2016)
The article discusses research on self-repairing robots. Topics include the use of three-dimensional (3D) printing to repair robots, the use of evolutionary design algorithms to deal with robot repair, and problems with simulation-based techniques. The issue of processing time to make decisions is addressed. Comments by researchers including Kyrre Glette, Jean-Baptiste Mouret, and David Johan Christensen are presented.